MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN MELALUI METODE PQ4R PADA PELAJARAN BAHASA INDONESIA SISWA KELAS V SD NEGERI 008 PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU - Tiflan, Tiflan (Aksara Public, 2017)
This research is motivated by the low ability students in reading comprehension. This study aims to determine whether the PQ4R method can improve reading comprehension in Indonesian Language Elementary School fifth grade students 008 Pagaran Tapah Darussalam Rokan Hulu. The subjects were 33 students in the academic year 2014-2015. Form of research is classroom action research. The data collection technique used is the technique of observation and tests reading comprehension. Based on the results, it can be concluded that through PQ4R method, it will be able to improve reading comprehension in the Indonesian language teaching fifth grade students of SD Negeri 008 Pagaran Tapah Darussalam Rokan Hulu. The results of observations of the early symptoms of reading comprehension of students obtained an average percentage of 69.3 with a low category. Then berdasarkam results of observations on the first cycle showed that the ability of Reading Comprehension students achieve with an average percentage of 75.1 in the medium category. While on the second cycle increased achieve reading comprehension of students obtained an average percentage of 85.3 with the high category.